Parent-Child Communication and Family Income as Predictors of Reproductive Health Service Utilization Among Adolescents in Akwa Ibom North-East Senatorial District - Udo, Grace Solomo; Ogbonda, Nkechinyere; Okankwu, Elizabeth Amini (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
The study examined the relationship between parent-child communication and family income as predictors of the utilization of reproductive health services among adolescents in Akwa Ibom North-East Senatorial District, Nigeria. A descriptive survey design was adopted, and a total of 500 adolescents constituted the sample, selected using a cluster random sampling technique. Two validated instruments Family Variables Questionnaire and Utilization of Reproductive Health Services among Adolescents Questionnaire were used for data collection. The reliability coefficients of the instruments were 0.82 and 0.75, respectively. Data collected were analyzed using the Pearson Product Moment Correlation (PPMC) statistical technique at a 0.05 level of significance. Findings revealed a very weak negative relationship between parent-child communication and utilization of reproductive health services (r = –0.11, p = 0.061), as well as between family income and utilization of reproductive health services (r = –0.11, p = 0.061). These results indicate that neither parent-child communication nor family income significantly influences adolescents’ use of reproductive health services in the study area. The null hypotheses were therefore accepted. The study concluded that variations in parent-child communication and family income do not significantly predict the utilization of reproductive health services among adolescents. It recommended strengthening parent-adolescent communication programs through workshops and counseling, promoting family-based and school-based interventions, subsidizing adolescent reproductive health services, and integrating socioeconomic and cultural considerations into public health policies. Further research was suggested to explore other social, cultural, and structural factors influencing adolescents’ access to reproductive health services.